Engineering eHeritage—A New Approach for Study of Intangible Cultural Heritage. Case Study: The Analysis of the Noise Produced by the Dacian Dracon - BUTNARIU Silviu (MDPI - Sustainability 2019, 2019)
Preserving the past is an important task of the current generation because of the rapid changes that influence our society. There are certain objects or traditions that make us feel as though we are part of something and—a country, a way of life. The term ‘cultural heritage’ has seen many changes over the last decades and can be evaluated from a tangible or intangible point of view. Since the beginning of the 21st century, the recognition and protection of intangible cultural heritage (ICH) has seen an increased importance. ICH includes goods that can express the idiosyncrasy of certain groups, represent a specific skill, or tradition. This paper presents a working methodology on a structured approach to ICH elements, as well as a case study of such an object. At the same time, this paper proposes a new method of artifacts research, an approach that brings, in addition to engineering, expertise from several fields: Mechanics, construction, material resistance, flow of fluids, heat transfer, ICT, and virtual reality.
Keywords: Engineering eHeritage; intangible cultural heritage; Dacian Dracon; acoustics